Developing Interactive Learning Media for Teaching Writing Descriptive Text in Senior High School - Jeni Haryati; Atni Prawati; Rumiri Aruan (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2023)
The advancements in technology make it unavoidable to be used as a teaching medium in education. Thus, this research aims to develop an interactive learning media in the form of an Android-based application as a teaching medium for writing descriptive texts in senior high school and to determine the validity of the media. The researchers applied the Research and Development (R&D) by employing the 4D Model developed by Thiagarajan et al. (1974). The instruments used were an interview, the validation sheets from a material expert, a media expert, and a learning expert (an English teacher), and a students’ response questionnaire. The research findings showed that the average result of the experts' assessment was 3.75 which was classified as 'Very Valid', then from the result of the students’ response questionnaire a percentage score of 81.19%, categorized as 'Very Decent’. Therefore, interactive learning media indicates valid and suitable to be utilized as teaching and learning media for writing descriptive texts for tenth-grade students in high school. The use of interactive learning media can be an alternative to attract students' interest in the learning process, especially in writing descriptive texts in a fun way.